Perilaku dan Peran Tokoh Masyarakat dalam Pencegahan dan Penanggulangan Pandemi Covid -19 di Desa Jayaraga, Kabupaten Garut - Udin Rosidin; Laili Rahayuwati; Erna Herawati (Umbara, 2020)
This study aims to describe behaviour and roles of community leaders in the Covid-19 prevention at Jayaraga Village, Garut District. This study applied qualitative method. Data were collected through discussion with community leaders who joined whatsapp group. This study reveals that the behaviour of community leaders is the product of their knowledge and attitude. They have sufficient knowledge about Covid-19 which in turns construct their attitude towards it. They worry about the disease its rapid contagion and its negative impact to the community. Having this attitude, they decided to start actions for prevention, and invited community members to join them in the action. They promoted healthy life behaviour, which is known effective in prevent the Covid-19 contagion, and initiated actions which aims to assist members of the community whose socio-economic condition devastated by the pandemic. The behaviour of these community leaders describes their roles in the community in the context of Covid-19 pandemic. This behaviour also enhances empowerment of the to Covid-19 pandemic.